Effect of Alpha-Lipoic Acid on the Characteristics and Physical Stability of NLC-Green Tea Extract - Fairuz Yaumil Afra; Widji Soeratri; Djoko Agus Purwanto (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: The addition of alpha-lipoic acid in Nanostructured Lipid Carrier-Green Tea Extract (NLC-GTE) has potential to increase effectiveness of anti-aging preparations. It happened because alpha-lipoic acid can increase stability and antioxidant activity. Objective: Comparing the physical characteristics and stability of NLC-GTE with or without alpha-lipoic acid. Methods: NLC-GTE manufactured using the High Shear Homogenization method. NLC-GTE was divided into two formulas, without the addition of alpha-lipoic acid for F1 and with the addition of alpha-lipoic acid for F2. The characteristics and physical stability were tested, including organoleptic, pH, particle size, and polydispersity index. Stability test was held using the thermal cycling method. Results: Based on characteristic test, it was found that F2 had larger particle size value than F1. The average particle size value of F1 is 313.9 ± 0.76 nm and 423.4 ± 0.75 nm for F2. The F1 and F2 preparations had a polydispersity index value below 0.3, so they were homogeneous. The average pH value of F1 is 5.998 ± 0.01, and F2 is 4.798 ± 0.004. The physical stability test showed a difference before and after the sixth day in particle size and pH, but it was still in the range, so it was safe. However, there was a separation in F1 after day 6. Conclusion: Based on the characteristics and physical stability tests, F1 (without alpha-lipoic acid) and F2 (with alpha-lipoic acid) had differences in particle size and pH. From the physical stability test, it can be concluded that F2 is more stable than F1.